2016
DOI: 10.1016/j.copbio.2016.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Into new territory: improved microbial synthesis through engineering of the essential metabolic network

Abstract: Advances in synthetic biology and metabolic engineering offer the promise of next generation bioprocesses to produce numerous products including specialty and bulk chemicals and even biofuels sustainably from renewable feedstocks. A primary challenge is the optimization of product flux, within a much larger and complex metabolic network. While simple gene deletion methods can be used in the case of non-essential byproduct pathways, more sophisticated approaches are required when competitive fluxes are essentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 48 publications
1
19
0
Order By: Relevance
“…While the expression of heterologous proteins during stationary phase may seem counterintuitive and at odds with maximal production, stationary phase cells can maintain significant metabolic activity and produce high levels of protein. [25][26][27][28][29] Specifically, phosphate depletion has been used routinely for heterologous protein expression. [30][31][32] In addition, it has been shown that phosphate depletion can be used to amplify the expression of heterologous proteins using the pET based T7 promoters in E. coli.…”
Section: Introductionmentioning
confidence: 99%
“…While the expression of heterologous proteins during stationary phase may seem counterintuitive and at odds with maximal production, stationary phase cells can maintain significant metabolic activity and produce high levels of protein. [25][26][27][28][29] Specifically, phosphate depletion has been used routinely for heterologous protein expression. [30][31][32] In addition, it has been shown that phosphate depletion can be used to amplify the expression of heterologous proteins using the pET based T7 promoters in E. coli.…”
Section: Introductionmentioning
confidence: 99%
“…These promoters (as well as insulated version) have utility in two-stage expression and production. 22,23 None of these 4 promoters were found to be robust to oxygen conditions, and optimal expression requires adequate culture aeration, limiting use in oxygen limited or anaerobic cultures.…”
Section: Resultsmentioning
confidence: 99%
“…To our knowledge this is the first combination of these two mechanisms to improve cellular lysis and DNA removal, and an example of the potential benefits of two stage production. [43][44][45] This system enables > 95% lysis and hydrolysis. Due to tightly controlled expression these strains are stable to shear forces in stirred tank bioreactors and even when subjected to freeze thaw cycles in deionized water, with 10% glycerol.…”
Section: Discussionmentioning
confidence: 99%